DNA methylation subclasses predict the benefit from gross total tumor resection in IDH-wildtype glioblastoma patients. Issue 2 (22nd July 2022) - Drexler, Richard; Schüller, Ulrich; Eckhardt, Alicia; Filipski, Katharina; Hartung, Tabea I; Harter, Patrick N; Divé, Iris; Forster, Marie-Therese; Czabanka, Marcus; Jelgersma, Claudius; Onken, Julia; Vajkoczy, Peter; et al.
Abstract: Background: DNA methylation-based tumor classification allows an enhanced distinction into subgroups of glioblastoma. However, the clinical benefit of DNA methylation-based stratification of glioblastomas remains inconclusive. Methods: Multicentric cohort study including 430 patients with newly diagnosed glioblastoma subjected to global DNA methylation profiling. Outcome measures included overall survival (OS), progression-free survival (PFS), prognostic relevance of EOR and MGMT promoter methylation status as well as a surgical benefit for recurrent glioblastoma. Results: 345 patients (80.2%) fulfilled the inclusion criteria and 305 patients received combined adjuvant therapy. DNA methylation subclasses RTK I, RTK II, and mesenchymal (MES) revealed no significant survival differences (RTK I: Ref.; RTK II: HR 0.9 [95% CI, 0.64–1.28]; p = 0.56; MES: 0.69 [0.47–1.02]; p = 0.06). Patients with RTK I (GTR/near GTR: Ref.; PR: HR 2.87 [95% CI, 1.36–6.08]; p < 0.01) or RTK II (GTR/near GTR: Ref.; PR: HR 5.09 [95% CI, 2.80–9.26]; p < 0.01) tumors who underwent gross-total resection (GTR) or near GTR had a longer OS and PFS than partially resected patients. The MES subclass showed no survival benefit for a maximized EOR (GTR/near GTR: Ref.; PR: HR 1.45 [95% CI, 0.68–3.09]; p = 0.33). Therapy response predictive value of MGMT promoter methylation was evident for RTK I (HR 0.37 [95% CI, 0.19–0.71]; p < 0.01) and RTK II (HR 0.56 [95% CI, 0.34–0.91]; p = 0.02) but not the MES subclass (HR 0.52 [95% CI, 0.27–1.02]; p = 0.06). For local recurrence (n = 112), re-resection conveyed a progression-to-overall survival (POS) benefit ( p < 0.01), which was evident in RTK I ( p = 0.03) and RTK II ( p < 0.01) tumors, but not in MES tumors ( p = 0.33). Conclusion: We demonstrate a survival benefit from maximized EOR for newly diagnosed and recurrent glioblastomas of the RTK I and RTK II but not the MES subclass. Hence, it needs to be debated whether the MES subclass should be treated with maximal surgical resection, especially when located in eloquent areas and at time of recurrence.